Social media analytics: how they support company public relations. Issue 1 (14th January 2019) - Tam, Lisa; Kim, Jeong-Nam
Abstract : Purpose: In the midst of practitioners' increasing use of social media analytics (SMA) in guiding public relations (PR) strategy, this paper aims to present the capabilities and limitations of these tools and offers suggestions on how to best use them to gain research-based insights. Design/methodology/approach: This review assesses the capabilities and limitations of SMA tools based on industry reports and research articles on trends in PR and SMA. Findings: The strengths of SMA tools lie in their capability to gather and aggregate a large quantity of real-time social media data, use algorithms to analyze the data and present the results in ways meaningful to organizations and understand networks of issues and publics. However, there are also challenges, including the increasing restricted access to social media data, the increased use of bots, skewing social conversations in the public sphere, the lack of capability to analyze certain types of data, such as visual data and the discrepancy between data collected on social media and through other methods. Originality/value: This review suggests that PR professionals acknowledge the capabilities and limitations of SMA tools when using them to inform strategy.